Lönsamhet i att avverka virkesrik fastighet innan försäljning - Jacobsson, Ludvig (2014)
The purpose of this study is to find out the viability in performing final felling in stands with high timber volume or if it´s more profitable to leave these stands to the next owner. Will he or she pay more for the standing stock then the industry? The prices of forest-land have increased significantly over the last couple of years in Sweden and some properties seem to go higher than others. Is this because of higher standing stock volume or can a certain volume/hectare bring a higher price? Maybe a combination of both? This study is based on the the sale-statistics for 2012 from real-estate agency Areal. The material was divided between different geographical areas. The calculations were only based on forest values. Such as: m³/hectares, SEK/m³sk and total standing stock. The study also consists of a literature-study and information from relevant internet-sites. The different geographical areas did not distinguish themselves so much from each other, except of course pricing. Low and high volume stands that differed significantly from average properties were paid less per m³sk. The one big difference that was found was in region 3, Värmland, Dalarna, Hälsingland and Gästrikland. In that region, properties with low average standing stock were paid higher per m³sk. In this region, 1 hectare with 5 m³, only cost half of 1 hectare with a standing stock of 100 m³sk. One might think that a hectare that’s consists of 20 times more wood should be paid 20 times higher? Especially when the most popular method of estimating value on forest-properties, is to take the total standing stock and multiplying it with the average market-price per m³.